Konstruksi Filsafat Barat Kontemporer - Syarifuddin Syarifuddin (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2011)
The Twentieth century man's life is full of various problems. According tophilosophers, the source of this complexity is the way some thinks. Therefore,they are very concerned to see man‟s life through the scientific method carefully.They began to study language, meaning, and symbols. They also examine the emotions that exist in humans as well as the attitude of human life. Therefore, the study of Contemporary Western philosophy is related to contemporary issues that are resolved fundamental answer by philosophers. Period of contemporary philosophy is usually still refers to the period of the nineteenth century to the present. Contemporary philosophy is still continuing major issues in modern philosophy, but with a different perspective altogether. Issues that include metaphysics, epistemology, anthropology (humanism) and others. In addition, a growing issue in contemporary philosophy extends to issues of capitalism, alienation, environment, democratization, human rights, and so forth. Many thinkers of the twentieth century thought has its own characteristics, namely "decentralization" of man. Human subjects are no longer regarded as the center of reality, but replace "anthropocentrism", the decentralization of human language as well as the subject of special attention to the fact.